Short Course by FK Reinforcement Learning on Video Game - Mritha, Ramalingam (Faculty of Computing, 2021)
PEKAN, 18 August 2021 - A short course training on Reinforcement Learning on Video Game was organized by FK and conducted virtually by FK academicians, Ts. Dr. Azlee Zabidi and Ts. Dr. Mohd Izham Mohd Jaya on 16-17 August 2021.